A Structural Equation Model of Individual Greenhouse Gas Emission Behaviours for Khon Kaen: A Low Carbon City - Srivongchai, Piti; Chamaratana, Thanapauge (The journal of contemporary issues in business and government, 2021)
This study investigates a structural equation model (SEM) of factors that influence individual greenhouse gas emission behaviours in the context of Khon Kaen city, northeast Thailand. The study discusses behavioural changes that are central to reducing greenhouse gas emission in a city. The study employs an exploratory, sequential mixed- method design. This qualitative study indicates that individual greenhouse gas emission behaviours consisted of seven conditions: Characteristics; knowledge; social support; motivation; attitudes; role models; and information. The model in the second phase fits with the empirical data, with p-value = 0.21758, Chi-Square/df = 1.134, GFI = 0.98, AGFI = 0.94, RMSEA = 0.019, and R2 = 0.88. It is found that social support, motivation, attitudes, and role models played a more important role for individual greenhouse gas emission behaviours with an effect size of 0.42, 0.34, 0.29, and 0.12, respectively. Meanwhile, characteristics, knowledge, and information did not affect individual greenhouse gas emission behaviours. The authors strongly suggest that environment preservation policies, especially behavioural changes to reduce greenhouse gas emission which place importance on people's knowledge amelioration and information publicity should be improved by focusing on developing social structures, strengthening motivations, enhancing people's attitudes, and increasing the number of role models.